ANTI-HISTAMINIC ACTIVITY OF UTHAMANI CHOORANAM (PERGULARIA DAEMIA) AGAINST HISTAMINE INDUCED PAW OEDEMA IN RATS - Jayasree, S.; Banumathi, V.; Gandhimathi, S.; Shameem, F. R. (International Journal of Ayurveda and Pharma Research, 2015)
Atopic dermatitis (AD) is a chronic relapsing, pruritic, inflammatory skin disease in children associated with personal or family history of other atopic disease like asthma, allergic rhinitis. Clinically characterized by itching, dryness, erythema, vesiculation, exudation and lichenification etc. The present treatment for AD in modern science is steroids or calcinueurin inhibitors. But repeated course of steroids can cause immuno suppression and growth retardation. The drugs in Siddha system of medicine is well known for their effectiveness and less toxicity. One such medicine is Uthamani Chooranam (UC) indicated for AD. The activity of UC was studied by using histamine induced paw oedema in rats by phenylbutazone. Exposure of rats hind paw to histamine resulted in marked increase of paw tissue weight and skin thickness. After oral administration of UC at various dose levels of 200mg/kg and 400mg/ kg reduce the paw volume when compared to control group. The present studies shown the Siddha drug UC is significantly reduce the paw oedema and this study supports the anti-histamine effect of UC.